Teachers’ Practices in Curriculum and Instruction in a Science High School Amidst the Covid-19 Pandemic - Bacosa, Dennis P.; Caballes, Dennis G. (International Journal of Humanities and Education Development (IJHED), 2022)
The disruptions caused by the Covid-19 Pandemic do not excuse science schools from continuing to provide holistic quality education to their learners. This study determined teachers' practices in the Curriculum and instruction as part of School-Based Management Level-3 of a public science high school. The descriptive-correlation quantitative research design and data triangulation were employed. The teachers were on average age of 32.90 years, 75% of the respondents were female, the average years in service of the teachers is eight years, and the majority are Teachers I-III, about 93.8% of the respondents. About 18.8% of the respondents were full-fledged in their Master's Program. Results of the study showed that teachers' overall level of practice in Curriculum and instruction was denoted as highly practiced. Correlational analyses revealed a significant relationship between the highest educational attainment and general practices of teachers in Curriculum and instructions (r=0.478,p=0.002<0.05). A significant relationship between the provision for the development needs of learners and the Review, improvement, and contextualization of assessment tools for teaching and learning as teachers' practices in the Curriculum and Instruction was also presented (r=0.449,p=0.010<0.05). A significant relationship between the regular collaboration of the learning system and the Review, improvement, and contextualization of assessment tools for teaching and learning (r=0.430,p=0.014< 0.05) was also significant.